2007
DOI: 10.1002/jmri.21142
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analyses of effects on visual and visuomotor performance from exposure to magnetic stray fields from MRI scanners: Application of the Bayesian framework

Abstract: Purpose: To pool measurement data from individual studies on acute and temporal neurobehavioral effects of stray fields and reanalyze these using a Bayesian framework. Materials and Methods:Data from tests assessing effects of exposure to stray fields (Ͻ1600 mT) from MRI systems (1.5-7.0 T) on visuomotor and visual sensory systems collected in three relatively small case-crossover studies of volunteers seated in the magnet stray field were analyzed together using hierarchical regression models. Bayesian prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…The control population in that study reported at least one SMF core and/or SMF target symptom in 1 % and 25 % of shifts, respectively. We did not observe an association of increased prevalence of symptoms with increasing exposure, which puts these results at odds with previous studies [6][7][8] and with experimental work [11,12,29,30]. Possibly this may be ascribed to the fact that the variation in exposure in our study was not large enough; we only had staff working with 1.5 T or 1.5 T and 3 T systems, while other studies included exposures ranging from 0 (non-exposed controls) up to 7 T. However, reporting of the reference symptoms decreased with increased magnet strength, which may suggest some residual confounding we could not correct for.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The control population in that study reported at least one SMF core and/or SMF target symptom in 1 % and 25 % of shifts, respectively. We did not observe an association of increased prevalence of symptoms with increasing exposure, which puts these results at odds with previous studies [6][7][8] and with experimental work [11,12,29,30]. Possibly this may be ascribed to the fact that the variation in exposure in our study was not large enough; we only had staff working with 1.5 T or 1.5 T and 3 T systems, while other studies included exposures ranging from 0 (non-exposed controls) up to 7 T. However, reporting of the reference symptoms decreased with increased magnet strength, which may suggest some residual confounding we could not correct for.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, for patients, unpleasant effects (dizziness and vertigo, for example, but also tachycardia and sweating), some of which are related to the static field, are reported more often during imaging using 7 T systems than with 1.5 T systems [9]. Some of these reported effects may be related to adverse effects on visual perception, spatial orientation, visuomotor performance, working memory, and attention, measured in controlled trials [10][11][12][13]. Experimental studies similarly show that exposure to the static magnetic field has a direct negative, but temporary, effect on the vestibular system [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…No significant effects on cognitive function were found at any field strength or condition [35 • ]. In contrast, studies by the group of De Vocht showed some small but significant effects on attention/concentration and visuospatial orientation when the subject was positioned in the stray field of a 7 T scanner both when stationary and also after moving their head [36,37]. Bearing in mind the recent studies, discussed previously, on nystagmus, it would be interesting to investigate whether this could explain the observed cognitive effects in the visuospatial and attention/concentration domain, and to replicate the possible relation between nystagmus and these cognitive effects in a magnetic field free environment during vestibular activation [38].…”
Section: Biological Effects Of the Main Magnetic Field Strengthmentioning
confidence: 89%
“…The (long-term) health significance of these acute neurobehavioral effects and reported symptoms among employees who repetitively work near MRI systems is as yet unknown. Nevertheless, these dose-dependent effects [15][16][17] could potentially lead to accidents and errors by workers that are harmful for themselves or for patients under their care, for example during MRI-guided interventional procedures. If the authors would have recognized these in their review they would have been able to update their 'conventional' safety recommendations with advice on how to limit the incidence of these transient effects among personnel and hence potential errors and accidents resulting from them.…”
mentioning
confidence: 98%